Answer:
1. (i) ×(Moles B)/(Moles A), (ii) ×(Molar mass B)
2. (i)/(Molar Mass A) , (ii)× (Moles B)/(Moles A), (iii) × 6.02×10²³
3 (i) /(Molar mass A) (ii) ×(Moles B)/(Moles A) (iii) ×(Molar mass of B)
Attached please find direct solution
Step-by-step explanation:
Here we have;
1. Moles A → (Moles B)/(Moles A)↔Moles B→(Moles B)×(Molar mass B)↔Mass B
2. Mass A → (Mass A)/(Molar Mass A) ↔Moles A → (Moles B)/(Moles A) ↔ Moles B → Moles B× 6.02×10²³ ↔ Particles of B
3. Mass A → (Mass a)/(Molar mass A) ↔ Moles A→(Moles B)/(Moles A) ↔ Moles B → (Moles B)×(Molar mass of B) ↔ Mass of B.